ANALISIS PENGARUH PENGIRIMAN, ATRIBUT PRODUK DAN WIRANIAGA TERHADAP KEPUASAN PELANGGAN BISNIS DAN DAMPAKNYA PADA KINERJA PEMASARAN PRODUK TISSUE PERUSAHAAN CV. INDO PRIMA DI PONTIANAK - B2041142028, KEVIN BENZ SUSANTO (Universitas Tanjungpura, 2017)
The purpose of this study was to determine and analyze the influence of delivery, product attributes and salesperson to customer satisfaction and impact on marketing performance. The collection of data through questionnaires and observation . The study population was a wholesaler outlet in Pontianak city. Data analysis using a SPSS version 17. Respondents about the variable delivery, product attributes, salesperson, customer satisfaction and marketing performance in this study are in the high category . The findings of this study indicate that only four hypothesis accepted that was product attributes and the salesperson are significantly influence the customer satisfaction, the salesperson and customer satisfaction are significantly influence the marketing performance. While three other hypothesis are rejected that was delivery not significantly influence the customer satisfaction, also delivery and product attributes not significantly influence the marketing performance. The magnitude of the effect of direct and indirect influences include: X1 à Y = 0,118, X2 à Y = 0,230, X3 à Y = 0,516, Y à Z = 0,776, X1 à Z = 0,040, X2 à Z = -0,099, X3 à Z = 0,301, the magnitude of the direct effect of delivery (X1), product attributes (X2), salesperson (X3) on marketing performance (Z) is smaller than the indirect effect delivery (X1) product attributes (X2), salesperson (X3) on marketing performance (Z) through customer satisfaction (Y) , where the direct influence of variables X1, X2 and X3 to variable Z at 0.040 , -0.099 and 0.301 with R2 was 0.074 , while the indirect influence of variables X1, X2 and X3 to variable Z through the variable Y was 0.092, 0.178 and 0.400 with R2 was 0.579. Keywords : Delivery, Product Attributes, Salesperson, Customer Satisfaction and Marketing Performance